BRIEF PSYCHOEDUCATION INTERVENTION AGAINST HIV/AIDS RELATED STIGMA AMONG HOUSE WIFES LIVED IN COFFEE PLANTATION AREA - Ahmad Rifai (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2016)
Background: HIV/AIDS resulted negative effects for last 29 years forwhole Indonesian society. It influenced not only in health sector, butalso improved problems in economic and social live. Most peoplebelieved that people lived with HIV/AIDS (PLWHA) acted andbehaved immorally which caused them got infected by this virus. Itleaded society keep the distance away from PLWHA and stigmatizedthem. HIV/AIDS related stigma impeded the access for PLWHAutilizing health care services and social respond.Objective: the study purposed to analyze effectiveness of briefpsychoeducation intervention to HIV/AIDS related stigma amonghouse wifes lived in coffee plantation area in Jember.Methods: this research was a quasy-experimental pre-post testdesign with control group. The total sample was 30 respondents whowere divided into intervention group and control group whichconsisted of 15 respondents in each group that were collected bysimple random sampling technique. T-test dependent andindependent were operated in data analysis.Results: there was significant difference of HIV/AIDS related stigmaamong house wifes before and after brief psychoeducation.intervention, and there was also difference between control andintervention group (p value = 0,000 ; CI 95% < alpha = 0,05).Conclusion: brief psychoeducation has positive effect in reducingHIV/AIDS related stigma among house wifes lived at coffeeplantation area. It is important for health care provider improvingand implementing the brief psychoeducation intervention forcommunity as supportive intervention to achieve zero stigma targetfor PLWHA.